Ipomoea batatas (L.) Lam. cultivation in the conditions of light culture in vitro and ex vitro - E. A. Kalashnikova; R. N. Kirakosyan; A. V. Gushchin; K. G. Abubakarov; N. N. Sleptsov; S. K. Temirbekova; A. P. Glinushkin; O. V. Meleshina; N. Ya. Rebouh; M. M. Tareeva (Овощи России, 2021)
Relevance. Currently, food products that include prebiotics, in particular, inulin, are particularly popular. Interest in this substance is justified by its valuable properties – it is a good immunomodulator, cleanses the body of toxins, radionuclides, "bad" cholesterol, promotes the assimilation of useful trace elements necessary for human life. Inulin is contained in plants such as jerusalem artichoke, chicory, as well as in sweet potatoes, the popularity of which is increasing every year. However, sweet potato plants are afraid of cold and frost-resistant. Therefore, the creation of new varieties and hybrids that are resistant to low temperatures is an urgent problem. Cellular biotechnology is aimed at solving this problem using methods of clonal microreproduction, cell selection, somatic hybridization, etc. For rapid reproduction and obtaining high-quality planting material, biotechnology methods are used, in particular, clonal micro-propagation. However, in this technology there are difficulties associated with poor adaptation of microclones to ex vitro conditions. This fact introduces an additional requirement for the selection of optimal rooting modes in vitro and ex vitro adaptation of microclones.Material and methodology. The aim of the work was to study the influence of cultivation conditions on in vitro rooting and ex vitro adaptation of I. batatas (L.) microclones. The object of the study was sweet potato microgears propagated in vitro. I. batatas micro-gears were cultured in vitro on a Murashige-Skug medium, differing by the type of auxins. The influence of red (R) and far red (FR) light on the shoots rooting in vitro and the adaptation of microclones ex vitro was studied.Results. It has been experimentally established that the cultivation of micro-gears on a medium containing indolyl butyric acid at a concentration of 0.5-1 mg/l and under conditions of illumination by LED lamps of red and far red light in equal amounts leads to the production of microclones with a well-developed root system and vegetative biomass. The use of an aeroponic installation at the last stage of clonal micro-propagation makes it possible to obtain high-quality planting material that can adapt well to open ground conditions.